2015
DOI: 10.3390/su7010747
|View full text |Cite
|
Sign up to set email alerts
|

Contextualism and Sustainability: A Community Renewal in Old City of Beijing

Abstract: Abstract:The conception of contextualism in community planning emphasizes the integrity of architecture and its surroundings. It also implies the sustainability of landscape meaning within a community. In as much as planning theories have not mentioned how extensive the background of a community should be considered by a community planner, this paper will seek to answer this question. It considers Nanluoguxiang (NLGX), a community in the old city of Beijing, as the study area. Based on government documents, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 25 publications
(26 reference statements)
1
19
0
3
Order By: Relevance
“…The 798 Art Zone has successfully regenerated cultural-led initiatives in abandoned cheap spaces through an environment conducive to creating, a flexible land system, and public policy [26,27]. Studies on urban regeneration in the Nanluoguxiang area revealed that the state and local governments' policies for urban conservation and residential renovation contributed greatly to the creation of distinctive landscapes, improvement of residential and regional environment, and the investment of private real estate in the area [13,28]. It was also discovered that the perception and attitude of residents affected the sustainability of regional development [29], and the Nanluoguxiang area was well preserved and even commercialized through long-term community regeneration projects [28].…”
Section: Culture-led Urban Regeneration In Beijingmentioning
confidence: 99%
“…The 798 Art Zone has successfully regenerated cultural-led initiatives in abandoned cheap spaces through an environment conducive to creating, a flexible land system, and public policy [26,27]. Studies on urban regeneration in the Nanluoguxiang area revealed that the state and local governments' policies for urban conservation and residential renovation contributed greatly to the creation of distinctive landscapes, improvement of residential and regional environment, and the investment of private real estate in the area [13,28]. It was also discovered that the perception and attitude of residents affected the sustainability of regional development [29], and the Nanluoguxiang area was well preserved and even commercialized through long-term community regeneration projects [28].…”
Section: Culture-led Urban Regeneration In Beijingmentioning
confidence: 99%
“…Суриков [2]. Зарубежные исследования направлены на изучение современной городской архитектуры в условиях устойчивого развития и сохранения наследия [3][4][5], а также на изучение социальных аспектов [6,7]. Многие исследования обращены к таким аспектам развития городской среды в условиях активного многоэтажного строительства как, например, уместность современных архитектурных вставок в исторические городские районы, важность сохранения территориальной идентичности в условиях вертикального развития городов [8][9][10].…”
Section: том 9 выпуск 2 (32)unclassified
“…В исследовании проводится анализ зданий в застройке исторического центра, превышающих параметры допустимой высотности и среднюю высотность кварталов, в которых расположены эти здания. При этом следует учитывать, что расхождение в допустимой и фактической высотности застройки кварталов объясняется годом утверждения Проекта зон охраны и более поздними Концепцией градостроительного развития и Генеральным планом города 3 . Поскольку невозможно дать однозначную оценку диссонирования или относительно гармоничного включения многоэтажного здания в исторический контекст, основываясь только на параметре высотности, в соответствии с задачами исследования также были рассмотрены особенности архитектурной композиции и размещения здания на участке и в застройке.…”
Section: результаты исследованияunclassified
See 1 more Smart Citation
“…In response to the above problems, scholars have proposed methods in terms of physical space redevelopment, collaborative planning with consensus and jointness [3,4], cultural-led and context-based regeneration [5,6], place quality, and environment content improvement to facilitate spontaneous and social activities [1]. Such practices explored available interventions and improved community vitality to some extent.…”
Section: Introductionmentioning
confidence: 99%